Prunus armeniaca Gum-Alginate Polymeric Microspheres to Enhance the Bioavailability of Tramadol Hydrochloride: Formulation and Evaluation - Shazia Noureen; Sobia Noreen; Shazia Akram Ghumman; Fozia Batool; Huma Hameed; Sara Hasan; Fozia Noreen; Mervat A. Elsherif; Syed Nasir Abbas Bukhari (MDPI AG, 2022)
Combinations of polymers can improve the functional properties of microspheres to achieve desired therapeutic goals. Hence, the present study aimed to formulate Prunus armeniaca gum (PAG) and sodium alginate microsphere for sustained drug release. Blended and coated microspheres were prepared using the ionotropic gelation technique. The effect of polymer concentration variation was studied on the structural and functional properties of formulated microspheres. FTIR, XRD, and thermal analysis were performed to characterize the microspheres. All the formulations were well-formed spherical beads having an average diameter from 579.23 ± 07.09 to 657.67 ± 08.74 μm. Microspheres entrapped drugs within the range 65.86 ± 0.26-83.74 ± 0.79%. The pH-dependent swelling index of coated formulations was higher than blended. FTIR spectra confirmed the presence of characteristic peaks of entrapped Tramadol hydrochloride showing no drug-polymer interaction. In vitro drug release profile showed sustained release following the Korsmeyer-Peppas kinetic model with an R2 value of 0.9803-0.9966. An acute toxicology study employing the oral route in Swiss albino mice showed no signs of toxicity. It can be inferred from these results that blending PAG with sodium alginate can enhance the stability of alginate microspheres and improve its drug release profile by prolonging the release time.